Return predictability and valuation ratios: Sector-level evidence on the Johannesburg Stock Exchange - Kudakwashe Joshua Chipunza; Hilary Tinotenda Muguto; Lorraine Muguto; Paul-Francois Muzindutsi (Cogent Economics & Finance, 2020)
The efficient market hypothesis describes an efficient market as one in which investors cannot consistently predict stock returns because prices instantly reflect all the information flowing into the market. However, return predictability has been documented in many markets. This study tests the predictability of returns using two valuation ratios-the dividend and earnings yields-on the South African market, at both aggregated and sectoral level. Unlike most studies in South Africa, this study employs an apposite present value model, accounts for structural breaks and investigates the non-linearity of the relationship between stock returns and valuation ratios. The results show that returns are predictable at both aggregated and sectoral levels. This finding has implications for market efficiency through enhanced price discovery which, in turn, has implications for investment and portfolio management. However, it should be noted that statistical significance may not translate to economic significance, so there is a need to determine the latter if one intends to use any strategy that relies on this evidence.
Keywords: G11; G12; G14; G15; 330; disaggregated data; dividend yield; earnings yield; present value model; Return predictability; South Africa